2010
DOI: 10.2114/jpa2.29.127
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Mild Stress (Hormetic Effects): Dietary Restriction and Health

Abstract: Hormesis is defined as a dose-response phenomenon characterized by low-dose stimulation and highdose inhibition, and has been recognized as representing an overcompensation for mild environmental stress. The beneficial effects of mild stress on aging and longevity have been studied for many years. In experimental animals, mild dietary stress (dietary restriction, DR) without malnutrition delays most age-related physiological changes, and extends maximum and average lifespan. Animal studies have also demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 61 publications
(58 reference statements)
2
40
0
1
Order By: Relevance
“…Furthermore, we found that HIF-1α and TERT expression and oxidative stress damage were parallel to the changes of telomere length. These findings support the beneficial effects of mild stress [29]. However, further studies are needed to explore alternative possibilities and elucidate the relationship between leukocyte telomere length and longevity in humans living at different altitudes.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, we found that HIF-1α and TERT expression and oxidative stress damage were parallel to the changes of telomere length. These findings support the beneficial effects of mild stress [29]. However, further studies are needed to explore alternative possibilities and elucidate the relationship between leukocyte telomere length and longevity in humans living at different altitudes.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, this early mild stress response with a subsequent adaption process supports the view that fasting may be a characteristic example of hormesis [24]. Extended fasting over at least 5-7 days is further associated with increases in concentrations of growth hormone, glucagon, and reductions of the blood levels of thyrotropin (TSH) and T 3 /T 4 [49,50].…”
Section: Mechanisms Of Fasting Effectsmentioning
confidence: 67%
“…Such a beneficial action and compensation of low-intensity environmental stressors can be classified as a hormetic response or hormesis, which describes a biological dose-response phenomenon characterized by low-dose stimulation and high-dose inhibition [24,25]. Other examples of moderate or intermittent stressors inducing hormesis are exercise, UV radiation, and ischemic preconditioning [26].…”
Section: Mechanisms Of Fasting Effectsmentioning
confidence: 99%
“…Reduction of inflammatory markers has been described in experimental studies [40]. To the contrary, shorter periods of fasting may lead to a mild stress or hormetic reaction [41] which is associated with increased circulating levels of catecholamines and thereby possibly leading to an acute phase response. Hormetic effects are characterized as an overcompensation of low dose stimulation and stress and are related to human health.…”
Section: Discussionmentioning
confidence: 99%